Penurunan Tekanan Darah dengan Pemberian Terapi Bekam pada Pasien Hipertensi Primer di Klinik Pengobatan Nabawi Al-Jundi Kota Bima Tahun 2019 - Ahmad Ahmad; Nurhasanah Nurhasanah; Martiningsih Martiningsih; A Haris A Haris; Nurwahidah Nurwahidah (Poltekkes Kemenkes Mataram, 2020)
Hypertension is one important factor as triggers not infectious disease that is currently a cause of death in the world number one.Cupping are other ways in the diagnosis and treatment ( unclassified diagnostic and treatment methods ) in its scope complementary therapy alternative. Cupping cause vasodilation general lowering blood pressure in a steady manner. Analytic research aims to know effectiveness cupping therapy to a decrease in pressure of patient hypertension in Treatment Nabawi Al-Jundi Bima City that collected with sheets of observation. Design used in this research was descriptive analytic with the design one group pre-post design. Way using the sampling purposive sample of samples from 33 respondents. Data analized t-test sample paired with a significant (a= 0,05). Research show that systolic blood peasure a patients before the first cupping 150 mmHg, decreased after second cupping being 130 mmHg, while dyastolic blood peasure a patients before the cupping 100 mmHg, decreased after second cupping being 90 mmHg. Research shows that cupping effektive in lowering systolic and dyastolic blood pressure with the p value = 0,000 (α < 0,05). Based on the research, cupping effektive in lowering blood prassure in patients hypertension at The Clinic Treatment Nabawi Al-Jundi Bima city